Hypertensive target organ damage in Ghanaian civil servants with hypertension. - Juliet Addo; Liam Smeeth; David A Leon (PLoS ONE)
Background Low levels of detection, treatment and control of hypertension have repeatedly been reported from sub Saharan Africa, potentially increasing the likelihood of target organ damage. Methods A cross-sectional study was conducted on 1015 urban civil servants aged > or = 25 years from seven central government ministries in Accra, Ghana. Participants diagnosed to have hypertension were examined for target organ involvement. Hypertensive target organ damage was defined as the detection of any of the following: left ventricular hypertrophy diagnosed by electrocardiogram, reduction in glomerular filtration rate, the presence of hypertensive retinopathy or a history of a stroke. Results Of the 219 hypertensive participants examined, 104 (47.5%) had evidence of target organ damage. The presence of target organ damage was associated with higher systolic and diastolic blood pressure levels. The odds of developing hypertensive target organ damage was five to six times higher in participants with blood pressure (BP) > or = 180/110 mmHg compared to those with BP < 140/90 mmHg, and there was a trend to higher odds of target organ damage with increasing BP (p = 0.001). Women had about lower odds of developing target organ damage compared to men. Conclusions The high prevalence of target organ damage in this working population associated with increasing blood pressure, emphasises the need for hypertension control programs aimed at improving the detection of hypertension, and importantly addressing the issues inhibiting the effective treatment and control of people with hypertension in the population.